2021
DOI: 10.1097/mou.0000000000000853
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of thulium fibre laser for treatment of urinary tract stones: results of a systematic review

Abstract: Purpose of review Lasers have become a fundamental aspect of stone treatment. Although Holmium:Yttrium-Aluminum-garnet (Ho:YAG) laser is the current gold-standard in endoscopic laser lithotripsy, there is a lot of buzz around the new thulium fibre laser (TFL). We decided to evaluate the latest data to help create an objective and evidence-based opinion about this new technology and associated clinical outcomes. Recent findings Sixty full-text articles and peer-reviewed abst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 62 publications
0
29
0
2
Order By: Relevance
“…The Moses technology has been shown to increase fragmentation and reduce retropulsion. There is now emergence of a thulium fiber laser (TFL) which allows improvements in ablation efficiency and retropulsion with the added advantage of portability, and while more clinical studies need to be done, it has increased the playing field of the laser market giving more choice to the endourologists [16]. Recently, a study from Russia showed the efficacy of TFL for ureteral stones with the authors recommending a setting of 0.5 J, 30 Hz for fragmentation and 0.15 J and 100 Hz for dusting [17].…”
Section: Emerging Advancements In Laser Techniques and Technologymentioning
confidence: 99%
“…The Moses technology has been shown to increase fragmentation and reduce retropulsion. There is now emergence of a thulium fiber laser (TFL) which allows improvements in ablation efficiency and retropulsion with the added advantage of portability, and while more clinical studies need to be done, it has increased the playing field of the laser market giving more choice to the endourologists [16]. Recently, a study from Russia showed the efficacy of TFL for ureteral stones with the authors recommending a setting of 0.5 J, 30 Hz for fragmentation and 0.15 J and 100 Hz for dusting [17].…”
Section: Emerging Advancements In Laser Techniques and Technologymentioning
confidence: 99%
“…28 In a randomized study, ThuFLEP was compared with HoLEP and MEP. 22 The authors found that ThuFLEP was associated with simple learning curve, achieving proficiency in as few as [8][9][10][11][12][13][14][15][16] procedures. This illustrates a key advantage over HoLEP which typically requires 50-60 procedures.…”
Section: Prostate Laser Enucleationmentioning
confidence: 99%
“…7,8 TFL has demonstrated efficacy and safety in ex vivo research and is now being deployed in clinical research. 9,10 One advantage of TFL is its higher water-absorption coefficient compared with Ho:YAG, which means that water absorbs TFL energy around four times higher than it does with Ho:YAG laser energy. Using water absorption as a model for cell absorption, the implication of this is that more energy from TFL is absorbed by cells and therefore they are better ablated.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of TFL by Kronenberg et al . [ 17 ] summarized that the ablation efficiency of TFL was two times faster for fragmentation and four times faster for dusting mode as compared to Ho:YAG laser. In our study also, when we compared the fragmentation mode of TFL with Ho:YAG laser in Miniperc, and we observed that the fragmentation was two times faster with TFL.…”
Section: Discussionmentioning
confidence: 99%